COMMERCIAL BANKS‘ACTIVITY DEPENDENCE ON MACROECONOMIC INDICATORS - Jureviciene, Daiva; Doftartaite, Dovile (European Scientific Journal, ESJ, 2013)
The purpose of the article is to assess the existence of dependence between commercial banks activity and macroeconomic indicators in Lithuania. Methods used: correlation and regression analysis of Baltic States commercial banks dependent variables (net profit, return of assets (ROA), return of equity (ROE), net interest margin (NIM) and independent country‘s macroeconomic indicators (GDP growth, foreign direct investment, average monthly gross salary, foreign trade balance, state budget, government debt, inflation and unemployment rate). Equations of correlation and regression analysis can be useful tool for planning a follow-up of commercial banks activities in Baltic States in short-term period. Correlation regression analysis was completed 4 times with 4 different dependent variables of Baltic States commercial banks. It was found out that the activities of Baltic States commercial banks dependence on macroeconomic indicators during investigated period differs.